Hubungan Aktivitas Fisik dan Tingkat Kebahagiaan Terhadap Daya Tahan Paru Jantung (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aims to analyze the effect of physical activity (X1) and happiness level (X2), both partially and simultaneously, on cardiorespiratory endurance (Y) in the elderly in Debululik Village, South Lamaknen District. The research method used is quantitative with an associative approach. The population in this study is the elderly in Debululik Village, with a sample size of 75 people taken using purposive sampling technique. Cardiorespiratory endurance was measured using the Six Minute Walk Test (6MWT), physical activity through a standardized questionnaire, and happiness level using a subjective well-being scale. Data analysis was carried out using multiple linear regression techniques through SPSS. The results of the study showed that, partially, physical activity did not have a significant effect on the cardiorespiratory endurance of the elderly (Sig. = 0.503 > 0.05). Partially, happiness levels do not have a significant effect on the cardiovascular endurance of the elderly (Sig. = 0.148 > 0.05); however, simultaneously, physical activity and happiness levels have a significant effect on the cardiovascular endurance of the elderly (Sig. < 0.05). This finding highlights the importance of a bio-psychosocial approach, where the synergy between mental motivation (happiness) and consistent physical movement is a key factor in maintaining cardiorespiratory efficiency in older adults.